Prediction of Asphaltenes Deposition in Multiphase Flow Systems through the use of Novel Numerical Modelling (Global Journal of Science Frontier Research, 2019)
One of the well-known problems encountered in oil flow lines, oil reservoirs and completion strings, causing flow assurance issues, is the deposition of asphaltenes in these areas. The complications aroused due to asphaltenes deposition include, but are not limited to, permeability reduction, wettability reversal, pipeline and well plugging, increased pressure drop and an overall reduction in oil production. The problem is not only severe, but it occurs so abruptly that it can damage the formation in a few days if it proceeds unnoticed. The asphaltenes deposition for a given oil is measured by the use of high-tech and expensive apparatuses, particularly where multiphase flow occurs, which incurs additional costs. Multiphase flow combined with asphaltenes precipitation worsens the situation in well bores and affects the flow of crude oil. This paper presents a numerical modeling approach for prediction of asphaltenes deposition and precipitation in crude oil in multiphase flow by the use of governing equations calculated using finite difference discretization methods.
Keywords: numerical modeling; asphaltenes precipitation; multiphase flow; enhanced oil recovery